Th2 inflammatory responses in the development of nasal polyps and chronic rhinosinusitis. Issue 1 (February 2020) - Ryu, Gwanghui; Kim, Dae Woo
Abstract : Purpose of review: Pathogenesis of nasal polyp has been largely studied based on innate and adaptive immunity of sinonasal mucosa. So far, various factors have been identified that trigger an inflammatory response in the pathogenesis of nasal polyps. In this review, we summarized recently updated information in the understanding of mechanisms in the development of chronic rhinosinusitis with nasal polyp (CRSwNP) focusing on Th2 inflammation. Recent findings: Endotype of CRSwNP presented mainly Th2-skewed inflammation, and it has been associated with refractoriness and comorbidities. Staphylococcus aureus can drive Th2 inflammation by producing enterotoxins and serine protease-like protein. Moreover, S. aureus directly affected mucosal barrier function and enhanced Th2 cytokine production by fast induction of epithelial-derived innate cytokines. Epithelial-derived innate cytokines, including TSLP, IL-25, and IL-33, promote Th2 responses via the development of innate lymphoid cells. Mast cell expresses IL-5, IL-13, and periostin, and it plays a role in the pathogenesis of nasal polyps through orchestrating eosinophil infiltration. Formation of eosinophil extracellular traps and Charcot–Leyden crystals is strongly associated with disease severity and viscous mucus plug production. Therefore, it needs to be investigated mechanistically. The role of neutrophils in Th2 inflammation has been poorly understood but appears to enhance Th2 inflammation and make it more resistant to steroid therapy. Summary: There is growing evidence of the role of S. aureus in innate and adaptive immunity, which contribute to Th2 inflammation in CRSwNP. Innate immunity, including epithelial-derived cytokines, plays a crucial role in the development of CRSwNP by inducing various pathways and need to be investigated more as Th2-targeted biomarkers. Recently, the role of neutrophilic inflammation in Th2 inflammation has started to be studied but still remains unclear.